2007
DOI: 10.1016/j.juro.2006.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Learning Curve for Holmium Laser Enucleation of the Prostate

Abstract: An endourologist inexperienced with holmium laser prostate enucleation can perform the procedure with reasonable efficiency after about 50 cases with an outcome comparable to that of experts, as described in the literature. During the learning curve conversion to transurethral prostate resection can be done without any harm to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 20 publications
7
121
0
3
Order By: Relevance
“…We found that reports based on subjective experience or confidence concluded that HoLEP competency required 20-30 cases of experience (6,11). On the other hand, reports based on enucleation efficacy concluded that at least 50 cases were needed to attain competency (12,13). Enucleation efficacy is considered to be a more objective parameter to estimate operative learning curve.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found that reports based on subjective experience or confidence concluded that HoLEP competency required 20-30 cases of experience (6,11). On the other hand, reports based on enucleation efficacy concluded that at least 50 cases were needed to attain competency (12,13). Enucleation efficacy is considered to be a more objective parameter to estimate operative learning curve.…”
Section: Discussionmentioning
confidence: 86%
“…Some researchers have argued that a surgeon needs between 20 and 30 cases of experience to attain competency (6,11), while others have argued that up to 50 cases are needed (12,13). This discrepancy comes mainly from the absence of an accurate way to evaluate the operative learning curve.…”
Section: Original Article Introductionmentioning
confidence: 99%
“…An average of 15-20 cases is needed for the trainee to feel confident with the technique [13]. However, others have reported that an endourologist inexperienced with HoLEP can perform the procedure with reasonable efficiency after about 50 cases, with an outcome comparable to that of the experts [14]. We feel that it is also important that learning the technique is easier if cases follow closely after each other to avoid relearning for every case.…”
Section: Technical Modifications and Their Advantagesmentioning
confidence: 99%
“…It has been recommended that a minimum of 50 procedures on smaller (o50 ml) prostate should be performed before larger prostate enucleations are attempted. 3 Photoselective vaporization of the prostate (PVP) using the 80-W potassium-titanyl-phosphate (KTP) laser was first reported in 2003 in a pilot study involving men with prostates sized 24-76 ml with good outcome and minimal morbidity. 4 The unique 532 nm wavelength that the laser operates at is highly absorbed by oxyhaemoglobin and minimally absorbed by water.…”
Section: Introductionmentioning
confidence: 99%